TEACHERS' SPIRITUAL COMPETENCE AND ITS IMPLICATIONS IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT STATE JUNIOR HIGH SCHOOL 2 LENGKONG NGANJUK - Muhammad Habibur Rochman; Zakariyah; Kabul; Muhamad Khaerul Hadi (Universitas Islam Lamongan, 2025)
Teachers have a lot of responsibility in the classroom since they guide students' spiritual development and assist them develop moral character. The spiritual competency of instructors and its effects on Islamic Religious Education instruction at State Junior High School (SMPN) 2 Lengkong, Nganjuk, are the subjects of this study. This research is grounded in a field study and employs a descriptive-qualitative analytic approach. The research subjects consisted of two teachers, the principal, the head of the MGMP (Teacher Working Group), and one student at SMPN 2 Lengkong, Nganjuk. Interviews, observations, document analyses, and focused-group discussions were used to gather the data. The results show that sincerity with which teachers educate their students is the source of their spiritual competency. To improve the learning process and its quality, teachers are primarily motivated by this sincerity to teach with all of their hearts, souls, responsibilities, and disciplines. Teachers of Islamic Religious Education are influenced by their spiritual competency, which also helps them carry out their responsibilities efficiently. Spiritual competency affects children’s morality and increases their motivation for academic success. Teachers thus provide appropriate direction, counseling, and positive role models for pupils in both classroom instruction and extracurricular activities.